Prove that:

1+2+3+4+5+6+.... up to infinity = -1/12 (negative of one-twelfth)

The above identity is used in many derivations of physics. I have a mathematical proof of the following, but please provide a logical one..

No vote yet

1 vote

×

Problem Loading...

Note Loading...

Set Loading...

$</code> ... <code>$</code>...<code>."> Easy Math Editor

`*italics*`

or`_italics_`

italics`**bold**`

or`__bold__`

boldNote: you must add a full line of space before and after lists for them to show up correctlyparagraph 1

paragraph 2

`[example link](https://brilliant.org)`

`> This is a quote`

Remember to wrap math in $</span> ... <span>$ or $</span> ... <span>$ to ensure proper formatting.`2 \times 3`

`2^{34}`

`a_{i-1}`

`\frac{2}{3}`

`\sqrt{2}`

`\sum_{i=1}^3`

`\sin \theta`

`\boxed{123}`

## Comments

Sort by:

TopNewestIt took me 1 day to personally find out the mistakes that the university professors have done. Those people forgot the basic conditions required for treating a series as converging infinite series. In short this was just one stupid act of getting fame

Log in to reply

are u sure???....could u show the proof???

Log in to reply

Please see my reply to Achint Gupta..

Log in to reply

Saw it...The numberphile video was amazing!!...Thanx!!

Log in to reply

hows this possible???? I mean sum of positive natural numbers is negative !!!!!! How ???

Log in to reply

Let S1 = 1 + -1 + -1 + 1 + -1 .....up to infinity = 1/2 (this can be proved by using the sum of infinite GP and even by simpler method. Let S2 = 1 -2 +3 -4 + 5 -6...up to infinity S2 + S2 = (1 -2 +3 -4....)+ (0 +1 -2 +3..) =S1 Therefore, 2 S2 = S1 = 1/2 Therefore, S2=1/4

Let S3 = 1 + 2 + 3 + 4 + 5.... Now, S3 - S2 = (1 + 2 + 3 +4...) -(1 -2 +3 -4..) = 4 + 8 + 12 +16..... = 4 (1+ 2 +3 +4...) = 4 (S3) Therefore, 3 (S3) = - S2 S3 = -1/12...

Sorry,I could not present it properly here.... For a better explanation , watch Numberphile on Youtube - https://www.youtube.com/watch?v=w-I6XTVZXww&list=TLB3KTqn9SZmDUThXfkDzwmDz8PRN0U-K-

Log in to reply

This stuff can never ever be proved by "using sum of infinite GP or by any other simple maths ". But I thank u for that video link which shows us but i cant understand it as it involves some higher mathematics which i haven't yet studied

Log in to reply

http://scientopia.org/blogs/goodmath/2014/01/17/bad-math-from-the-bad-astronomer/

Log in to reply

Log in to reply

Log in to reply

Log in to reply

S1 = 1 + -1 +1 + -1 ...... S1 + S1 =( 1 + -1 + 1 + -1 + ...)+ ( 1 + -1 + 1 + -1...) 2 (S1) = 1 S1 = 1/2 ..Hence...

Log in to reply

hey, that was grt proof.

Log in to reply

Log in to reply